Analisis Penerapan Standar Operasional Prosedur (SOP) dan Disiplin Kerja dalam Meningkatkan Efektivitas Kinerja Karyawan: Studi Kasus pada PT. HATNI - Nimas Ayunda (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to analyze the implementation of Standard Operating Procedures (SOP) and work discipline in improving employee performance effectiveness at PT. HATNI, a company engaged in fish processing and freezing. The research focuses on the security and production divisions, employing a qualitative method through observation and in-depth interviews with management and employees. The findings indicate that the absence of a structured SOP in the security division has led to inconsistent task execution and low levels of work discipline. Furthermore, the lack of formal training in the production division hinders the improvement of employee skills and motivation. This research resulted in the design of an SOP for the security division and recommendations for regular training programs in the production division. The implementation of these two strategies is expected to enhance discipline, productivity, and overall employee performance effectiveness, while strengthening the human resource management system at PT. HATNI.